grainBirds: Evolutionary granular synthesisers distributed in Fog Computing - Manzolli, Jônatas; Constantino, Edelson Henrique (Anais do Simpósio Brasileiro de Computação Musical (SBCM); 2021: Anais do XVIII Simpósio Brasileiro de Computação MusicalDO - 10.5753/sbcm.2021.19432, 2021)
The article presents the grainBIRD concept inspired by a distributed fog of grain sounds metaphor. Shortly, granular synthesizers are distributed in a mobile devices network. Applying Interactive Genetic Algorithm (IGA) and exchanging Open Sound Control (OSC) messages in a Virtual Private Network, grainBIRDs generate sound grains in standalone and network configurations. The grainBIRDs concept dialogues with the Internet of Things (IoT) paradigm since it was inspired by Cloud and Fog computing architectures. In this sense, this article presents the grainBIRD and grainBIRD Orchestra concepts, followed by a review on Computer Music and Network technologies related to the project. The article also discusses the computer implementation of the grainBIRD application using the Pure Data programming environment and concludes with performance tests of the network communication feasibility and the system sound generation capacities.